Full optical preparation of an absolute ground-state ultracold CsYb molecule via laser-assisted self-induced Feshbach resonance. (5th October 2022) - Sun, Zhi-Xin; Lyu, Bing-Kuan; Wang, Gao-Ren; Cong, Shu-Lin
Abstract: We investigate theoretically the formation of an ultracold CsYb molecule in the absolute ground state by full optical control. The laser-assisted self-induced Feshbach resonance takes place when the trap state in the optical lattice is coupled with a rovibrational state of the ground electronic state. The Feshbach molecule is formed in the resonant rovibrational state via an adiabatic population transfer by ramping the frequency of a chirped pulse. Two schemes are designed to prepare the absolute ground-state molecule starting from the Feshbach molecule: a pump–dump scheme controlled by short pulses and a stimulated-Raman-adiabatic-passage (STIRAP) scheme steered by long pulses. The probabilities of converting the Feshbach molecule to the absolute ground state molecule by using the pump–dump and the STIRAP schemes are 16% and 99%, respectively.